Analysis of Factors Influencing Consumer Decision to Purchase Le Minerale in Depok - Salma, Saffanah (Business Education Program of Universitas Pendidikan Indonesia, 2022)
This purpose of this research is to know what factors that influencing consumers decision to purchase Le Minerale in Depok. The type of this research is a quantitative descriptive study. The population of this research is the residents DepokAge 16 – 24 years old (Gen Z). Sampling using purposive sampling which is included in the type of nonprobability sampling technique with a minimum sampling size determined using the iteration formula (n: 117). Data collection techniques through questionnaires and Forum Group Discussion (FGD). The questionnaire was tested by using Pearson product moment validity test and reliability test using Alpha Cronbach formula. The results showed that residents of Depok price is the most influential factor in making purchasing decisions for Le Minerale,, and for the results of the product analysis, it has an influence in making purchasing decisions, last but not least is promotion, we know that promotion is also a factor that influences decisions purchase Le Minerale.